2017
DOI: 10.1002/ange.201700958
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric Total Synthesis of Hispidanin A

Abstract: Asymmetric total synthesis of the dimeric diterpenoid hispidanin A was accomplished by non‐catalytic Diels–Alder cycloaddition at room temperature. The synthesis relies on iron‐catalyzed coupling to construct a Z‐configured trisubstituted alkene, an iron‐catalyzed radical cascade to generate a labdane‐type diene, and both Yamamoto cationic polyene cyclization and palladium‐catalyzed Stille coupling to generate a totarane‐type dienophile.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 73 publications
0
3
0
Order By: Relevance
“…(E)-and (Z)-stereocomplementary second-step Suzuki-Miyaura cross-coupling using α-chloro-β-tosyloxy-α,β-unsaturated esters. [36,37] and γhydroxybutenolides (Schützenmeister's group). [38]…”
Section: Utilization By Other Groupsmentioning
confidence: 99%
See 1 more Smart Citation
“…(E)-and (Z)-stereocomplementary second-step Suzuki-Miyaura cross-coupling using α-chloro-β-tosyloxy-α,β-unsaturated esters. [36,37] and γhydroxybutenolides (Schützenmeister's group). [38]…”
Section: Utilization By Other Groupsmentioning
confidence: 99%
“…That is γ‐aminobutanoic acid (GABA) analogues (Merck's group), [11a] juvenile hormones 0 and I (Shinada's group), [32] deuterium‐labelled geranylgeraniols (Shinada's group), [33] functionalized steroids (Mazet and Li), [34] madangamine A (Chida's group), [35] asymmetric total synthesis of hispidanin A and related diterpenoids (Liu and Qin's group), [36,37] and γ‐hydroxybutenolides (Schützenmeister's group) [38] …”
Section: Utilization By Other Groupsmentioning
confidence: 99%
“…[9] Theg roup of Baran was the first to develop ag eneral coupling reaction using electron-deficient alkenes as the electrophilic component in both intra-and intermolecular variants in the presence of iron catalysts (Scheme 1Ab). [10] Anumber of other methodological procedures (e.g.,Scheme 1Ac), [11] as well as applications of HATpromoted C À Cb ond formation in natural product synthe-sis, [12] have been subsequently reported. Nevertheless,todate the HAT-initiated process has not been applied to reductively couple alkenes to ketones,d espite the carbonyl group being one of the most common unsaturated groups.W hile radical cyclization onto aC = O p-bond is facile,r ate studies have shown that ring closure of radicals onto carbonyl groups is slower than ring opening of the alkoxy radical counterparts, [13] thus rendering carbonyl groups generally unfavorable as radical acceptors.T his unfavorability is reflected by the limited use of radical cyclizations, with ketones as radical acceptors,t oa ccess cycloalkanols,a lthough in isolated examples haloalkanes, [14] av inylbromide, [15] alkynes, [16] and epoxides [17] have been used as proradicals.…”
mentioning
confidence: 98%